Determinan Stunting pada Balita di Wilayah Kerja Puskesmas Klampok 2 Kabupaten Banjarnegara - Pelangi Jiwa Aobama; Dedy Purwito (Jurnal Keperawatan Muhammadiyah, 2020)
Objective:to find out the determinants of stunting in the working area of Puskesmas (Public Health Care Center) of Klampok 2 in Banjarnegara Regency.Method: this was quantitative research with a case-control approach. There were 90 respondents as the samples of this research who were taken using a cluster sampling technique. The instruments of this research were questionnaires and the statistical tests were Chi-square and logistic regression tests.Results: There was no correlation between mothers' nutrition status during pregnancy and stunting (p-value 0.079). But, there was correlation between mothers education level (p-value 0.019), mothers knowledge level (p-value 0.016), breastfeeding (p-value 0.009), complementary foods (p-value 0.020), disease infection (p-value 0.002), family economy(p-value 0,017 ), family environment(p-value 0.011) and stunting. The most affecting factor was breastfeeding.Conclusion: Babies at the age of 0-6 months only need breast milk to fulfill their need for nutrition, therefore it should be the mothers' concern to provide breast milk so their baby will not experience stunting.